Letter (copy) : Basque Children - Tewson, Vincent
1939-11-10 038-0066-001 Secretary's. HVT/FC/EK/301. 10th November, 1939. Mr. J. Brotherton, Leeds Trades and Labour Council, 12, Camden Street, Beeston Hill, LEEDS. Dear Mr. Brotherton, BASQUE CHILDREN. I am in receipt of your letter of the 8th instant enclosing a resolution passed by your Trades Council in regard to the above subject. This question is being dealt with fully by the National Committee for the Care of Basque Children on which the General Council are represented. I am not aware of the evacuation centres in which Basque children still remain, but I do know that in some areas they have been evacuated with the British children. I think you can safely leave it to the National Committee to deal with this matter. Yours sincerely, Assistant Secretary. 292/946/38/66(I)